Lactose and Lactose Derivatives - Seval Andiç; Şehriban Oğuz (Turkish Journal of Agriculture: Food Science and Technology)
Milk is an important food substance and has a complex polydisperse system. The main components of milk consist of lactose, protein, and lipids. Mineral substances and vitamins are also present in milk as minor nutrients. Lactose known as milk sugar is the only carbohydrate in milk and it consists of glucose and galactose. The content of lactose in milk has varied according to milk types. Moreover, it is the most important energy source during the first years of human life, providing almost half of the total energy needed by newborns. Lactose is obtained industrially from the residues of cheese and casein production processes. Lactulose, lactitol, lactobionic acid, galactooligosaccharide, lactosucrose, epilactose, and tagatose are commonly known lactose derivatives. These derivates are produced from lactose using various methods such as epimerization, oxidation, and reduction. In this review, up-to-date information about lactose, lactose derivatives, and the production methods of lactose derivatives are given.